APPLICATION OF A BIODEGRADABLE MATERIAL FOR BONE REPLACEMENT IN TRAUMATOLOGY - T. V. Druzhinina; K. V. Trofimov; V. F. Naydanov; A. V. Rostovzev; D. V. Burkov; A. V. Zhulyabin; A. A. Isupov; A. V. Verevin (Бюллетень сибирской медицины, 2014)
20 men (medium age (31.5 ± 13.5) years) were studied. All patients underwent arthroscopic auditing plastic anterior cruciate ligament of the knee. Osteoregeneration dynamics were determined by biochemical testing of blood serum and X-ray computed tomography (CT) of the fracture in 1–4 months after surgery. As a result, an estimation of the bone tissue reparative regeneration according to CT data in 10 patients with a defect of the patella, treated with the material is provided. The obtained results of the clinical study indicate the reparative effect of the biodegradable material for bone replacing on bone regeneration